Exploring the different ways of small-town development in Central and Eastern Europe - Máté, Éva; Trócsányi, András (Journal for Geography, 2025)
Small town research represents a dominant part in urban geography. Being a transitional settlement type between urban and rural landscapes, it is important to define the roles of small towns regarding economy, services and infrastructure, recreation, or simply by their representations and identity. In this article, we aim to provide an insight into small town research in Central Eastern Europe and beyond, based on a 2024 summer school, focusing on the changing development paths of small towns.
Keywords: small town; Central Eastern Europe; development